Cirurgia conservadora, radioterapia externa e reforço de dose com braquiterapia de alta taxa de dose: uma nova perspectiva no tratamento de sarcomas de partes moles do adulto - Pellizzon, Antonio Cássio Assis (2002)
PURPOSE: To evaluate the influence on local control in adult patients with soft tissue sarcomas of the limbs that underwent limb-sparing surgery and high-dose rate brachytherapy (HDRB) in association with teletherapy. MATERIAL AND METHODS: Sixteen patients treated from 1993 to 1999 were reviewed. Teletherapy was used pre- or postoperatively (30--55 Gy) in association with HDRB in a dose range of 18--36 Gy (fx 3--6 Gy BID). The linear quadratic model was used to calculate the biological effective dose (BED) and the values obtained were compared with data from the literature, of studies that employed teletherapy and low-dose rate brachytherapy (LDRB). RESULTS: Soft tissue sarcomas BED mean and median values were 78.5 Gy7 and 80 Gy7, respectively. Univariated analysis showed that BED for patients with soft tissue sarcoma of the limbs submitted to HDRB was similar to the value of 83 Gy7 of patients submitted to LDRB (p = 0.008). Actuarial local control, disease free and overall survival rates at 5-years were 83.2%, 75% and 93.7%, respectively. CONCLUSIONS: HDRB appears to be an effective complementary method to teletherapy in the treatment of soft tissue sarcomas. The local control rates are comparable to those reported in the literature. However, studies with longer follow-up and a larger number of patients are still necessary in order to determine the true potential of HDRB as a substitute for LDBR.